2019
DOI: 10.1186/s12544-019-0356-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of innovative ideas for Public Transport proposed by citizens using Multi-Criteria Decision Analysis (MCDA)

Abstract: Introduction: The use of participatory techniques in the field of transport is coming to the forefront recently. In this frame, eight co-creation workshops and five online crowdsourcing campaigns took place in Thessaloniki, Southern Tuscany, Rotterdam/The Hague, and Frankfurt, from which many innovative ideas to enhance Public Transport were generated by citizens. Purpose: A simple list of innovations would not be very useful for Public Transport Operators, as they cannot implement all of them at once. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Ghorbanzadeh et al [30], in their study of evaluation public bus transport supply quality improvement in Mersin, Turkey, conducted interval AHP approach, 24 criteria and subcriteria were estimated. Nalmpantis et al [46] have proposed AHP approach to evaluate a set of innovation ideas for enhancing public transportation system and make it more attractive, the suggestions were recommended by the users and non-users.…”
Section: Literature Review On Mcdm Methodologies and Public Transportmentioning
confidence: 99%
“…Ghorbanzadeh et al [30], in their study of evaluation public bus transport supply quality improvement in Mersin, Turkey, conducted interval AHP approach, 24 criteria and subcriteria were estimated. Nalmpantis et al [46] have proposed AHP approach to evaluate a set of innovation ideas for enhancing public transportation system and make it more attractive, the suggestions were recommended by the users and non-users.…”
Section: Literature Review On Mcdm Methodologies and Public Transportmentioning
confidence: 99%
“…The service combines public transport, car sharing, a rental car service, taxis and a bicycle system-all in one smartphone app, all on one invoice, with 24/7 support and bonus points for sustainable transport choices. This form of solution is currently widely discussed both by researchers and by practitioners, and has also recently been rated by experts as their top choice [35]. However, concerns have been raised about its effectiveness with respect to sustainability as it may sometimes lead to increased car use; some subscribers take the opportunity to test new cars out of curiosity, resulting in rebound effects once again [36].…”
Section: The Intervention and Public Versus Car Transportmentioning
confidence: 99%
“…Many existing studies analyzed the factors influencing residents' mode choice concerning all modes available including CB based on the questionnaire surveys using discrete choice models [22][23][24][25]. Besides, Nalmpantis et al revealed that utility, as well as feasibility and innovativeness were promising criterions to make public transport more attractive [26]. Tsafarakis et al also concentrated on differences in user preferences along with public transport innovations in European cities [27].…”
Section: Literature Reviewmentioning
confidence: 99%